Ocular Effects of Behavior Management Medications. - Howell, Angela (Journal of Behavioral Optometry, 2012)
Background: Medications are often recommended for patients to control unwanted behaviors. Treatment with prescription drugs for autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and acquired brain injury (ABI) has benefits and side effects. Gains may be made in attention and mental focus while accommodation and eye tracking may be compromised. Benefits versus side effects must be considered when managing these conditions with drugs. Case Summary: A five-year-old girl presented for preschool evaluation. She destroyed the tape in the audio tape player in the waiting room, broke several legos, tore pages from the children's books and magazines and spilled a soda before being called back for her exam. History was positive for Rett's syndrome. No medications were taken. All examination parameters were within normal limits. The following year she returned complaining of difficulty reading and focusing at near. She managed to sit quietly in the waiting area and play with a puzzle before her eye exam began. The history revealed that she had started taking Prozac orally during the school year. Her mother reported that she read constantly. Reading material was constantly held close. She became aggressive when challenged to move it away. Exam findings showed distance visual acuities at 20/20 and near acuities reduced to 20/50. Accommodative testing showed reduced amplitude. A near prescription of +1.00 OU was recommended to assist in her reading focus. Conclusion: Behavior modifying medications were used to help this child and manage behavior in the classroom. Reduced accommodation is a known side effect of many commonly used drugs in the treatment of disorders such as ASD, ADHD, and ABI. Awareness of these medications and their side effects is warranted by eye care providers.